2020
DOI: 10.20870/oeno-one.2020.54.2.2948
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the mannoproteins of different strains of <em>Starmerella bacillaris</em> used in single and sequential fermentations on foamability, tartaric and protein stabilities of wines

Abstract: Aim: In this work, seven strains of Starmerella bacillaris were analysed for their ability to release polysaccharides during alcoholic fermentation (AF), both in single-strain and in sequential AF together with Saccharomyces cerevisiae.Methods and Results: A synthetic polysaccharide-free must was used to characterise the mannoproteins (MPs) released. The MPs were quantified, characterised in terms of carbohydrate composition, and tested to assess their ability to reduce protein and tartrate instabilities and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…According to the behaviors of yeasts cultivated in either synthetic or grape must, Brettanomyces bruxellensis , Hanseniaspora uvarum , Metschnikowia pulcherrima , Pichia fermentans , Saccharomycodes ludwigii , Schizosaccharomyces japonicas/pombe , Torulaspora delbrueckii , and Zygosaccharomyces bailii could produce nearly two times or even higher amount of MPs than their S. cerevisiae counterparts in the single inoculation experiments (Belda et al., 2015, 2016; Benito et al., 2019; Domizio et al., 2014, 2017; Giovani et al., 2012). Besides, the results of sequential inoculation among yeasts of different species indicate that the sequential inoculation is also an applicable method to promote the production of MPs, even for some yeasts ( Starmerella bacillaris ) that produced low amount of MPs in the single inoculation (Belda et al., 2015; Benito et al., 2019; Junior et al., 2020; Moreira et al., 2022). After ascertaining the acceptability, functionality and safety of these new MP products in a laboratory scale, the exploration of proper preservation/cultivation conditions and inoculation methods to satisfy the needs of specific non‐ Saccharomyces yeasts for the maximum MPs production should be the key points of the investigations in the future, in order to establish a yeast cultivation system for the production of MPs in an industrial scale.…”
Section: Development and Application Of Mp Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the behaviors of yeasts cultivated in either synthetic or grape must, Brettanomyces bruxellensis , Hanseniaspora uvarum , Metschnikowia pulcherrima , Pichia fermentans , Saccharomycodes ludwigii , Schizosaccharomyces japonicas/pombe , Torulaspora delbrueckii , and Zygosaccharomyces bailii could produce nearly two times or even higher amount of MPs than their S. cerevisiae counterparts in the single inoculation experiments (Belda et al., 2015, 2016; Benito et al., 2019; Domizio et al., 2014, 2017; Giovani et al., 2012). Besides, the results of sequential inoculation among yeasts of different species indicate that the sequential inoculation is also an applicable method to promote the production of MPs, even for some yeasts ( Starmerella bacillaris ) that produced low amount of MPs in the single inoculation (Belda et al., 2015; Benito et al., 2019; Junior et al., 2020; Moreira et al., 2022). After ascertaining the acceptability, functionality and safety of these new MP products in a laboratory scale, the exploration of proper preservation/cultivation conditions and inoculation methods to satisfy the needs of specific non‐ Saccharomyces yeasts for the maximum MPs production should be the key points of the investigations in the future, in order to establish a yeast cultivation system for the production of MPs in an industrial scale.…”
Section: Development and Application Of Mp Productsmentioning
confidence: 99%
“…Mannoproteins (MPs) are yeast cell wall (YCW) components released from yeasts either during alcoholic fermentation (AF) or aging on lees process (AOL) (Escot et al., 2001; Feuillat, 2003; Guadalupe & Ayestarán, 2007; Rigou et al., 2021) and can take 20–40% of the total red wine polysaccharides (Doco et al., 1996, 1999; Vidal et al., 2003b). During winemaking, the selection of MP‐overproducing yeasts are nowadays considered by many winemakers, and the AOL accompanied with the batonnage technique (stirring the lees at the bottom of the wine aging vessels periodically) to accelerate the degradation of lees (mainly consist of dead yeast cells and grape tissues) and to promote the release of MPs has been traditionally adopted, because MPs had been found effective in preventing the formation of tartaric crystals and protein hazes, and improving wine mouth‐feel sensation (Belda et al., 2015, 2016; Benito et al., 2019; Braschi et al., 2019; Caridi, 2006; Charpentier et al., 2004; Domizio et al., 2014, 2017; Dupin et al., 2000; Escot et al., 2001; Fornairon‐Bonnefond et al., 2002; Lankhorst et al., 2017; Leãoe et al., 2020; Moreira et al., 2022; Pérez‐Serradilla & De Castro, 2008; Waters et al., 1994). In recent decades, many researchers have reported that MPs can also interact with wine pigments and volatile compounds, which indicate a multifunctional role of MPs in modulating wine organoleptic properties (Alcalde‐Eon et al., 2014, 2019a, 2019b; Escot et al., 2001; Ghanem et al., 2017; Guadalupe & Ayestarán, 2008; Guadalupe et al., 2007, 2010; Rinaldi et al., 2012, 2019; Rodrigues et al., 2012a; Zhang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Yeast polysaccharides have been the most studied polysaccharides, especially MPs. Different authors found that MPs were more efficient in improving the tartaric stability [ 16 , 17 , 18 , 19 ] and protein stability of white wines [ 17 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…During grape must fermentation, it has been tested in both sequential and mixed yeast inoculations with S. cerevisiae (Rantsiou et al, 2012;Wang et al, 2014;Englezos et al, 2016;Lemos Junior et al, 2016). Many studies indicate that the use of S. bacillaris, together with S. cerevisiae, influences wine stability and enhances the glycerol content of wines with moderate volatile acidity production; wine flavour and mouthfeel are improved and, due to the low ethanol yield, ethanol content is reduced (Rantsiou et al, 2012;Englezos et al, 2016;Lemos Junior et al, 2016;Varela and Borneman, 2017;Lencioni et al, 2018;Lemos Junior et al, 2020a). Recently, the whole genome comparison of two S. bacillaris strains shed some light on genes responsible for yeast technologically relevant properties in winemaking (Lemos Junior et al, 2018).…”
Section: Introductionmentioning
confidence: 99%